INTEGRASI ASPEK HUKUM DALAM PENENTUAN ZONASI PESISIR UNTUK BUDIDAYA RUMPUT LAUT KABUPATEN BONE - Ahmad Suryadi; Muh. Ikhsan Idrus (JOURNAL IURIS SCIENTIA, 2026)
Marine spatial planning is a strategic instrument in supporting sustainable, equitable, and legally certain marine resource management. In its implementation, marine spatial governance in Indonesia still faces various issues, particularly normative conflicts and overlapping authorities among legal regimes that create legal uncertainty in marine space utilization. These problems are influenced by the fragmentation of regulations between spatial planning law, marine law, and various sectoral regulations that have not been systemically integrated, including the implementation of the Coastal Zone and Small Islands Zoning Plan (RZWP3K) and the Approval for Marine Space Utilization Activities (PKKPRL) mechanism. This condition has resulted in the suboptimal determination of coastal zone zoning to support the suitability of seaweed aquaculture in Bone Regency. This study aims to analyze the integration of legal aspects in determining coastal zones within marine spatial planning, assess the position and function of PKKPRL in the national marine spatial planning system, and formulate a legal integration model that supports the suitability of seaweed aquaculture in Bone Regency. This study employs a normative legal research method with statutory, conceptual, systemic, and comparative legal approaches. The results indicate that marine spatial planning problems are structural and functional due to the lack of synchronization in inter-sectoral regulations, weak harmonization of authority, and the non-integration of coastal zoning planning with marine space utilization licensing mechanisms. Furthermore, the implementation of RZWP3K has not been fully capable of accommodating legal certainty in marine space utilization for seaweed aquaculture activities. Therefore, integrated marine spatial planning regulations are required through the harmonization of legal norms, strengthening the position of PKKPRL, and synchronizing coastal zone zoning policies to create legal certainty, effective marine spatial planning, and sustainable seaweed aquaculture development in Bone Regency